Lung cancer treatment and mortality for Aboriginal people in New South Wales, Australia: results from a population-based record linkage study and medical record audit. Issue 1 (December 2016) - Gibberd, Alison; Supramaniam, Rajah; Dillon, Anthony; Armstrong, Bruce; O'Connell, Dianne
Abstract Background The aim of this study was to compare surgical treatment received by Aboriginal and non-Aboriginal people with non-small cell lung cancer (NSCLC) in New South Wales (NSW), Australia and to examine whether patient and disease characteristics are associated with any disparities found. An additional objective was to describe the adjuvant treatments received by Aboriginal people diagnosed with NSCLC in NSW. Finally, we compared the risk of death from NSCLC for Aboriginal and non-Aboriginal people. Methods We used logistic regression and competing risks regression to analyse population-based cancer registry records for people diagnosed with NSCLC in NSW, 2001–2007, linked to hospital inpatient episodes and deaths. We also analysed treatment patterns from a medical record audit for 170 Aboriginal people diagnosed with NSCLC in NSW, 2000–2010. Results Of 20, 154 people diagnosed with primary lung cancer, 341 (1.7 %) were Aboriginal. Larger proportions of Aboriginal people were younger, female, living outside major cities or in areas of greater socioeconomic disadvantage, smoking at the time of diagnosis and had comorbidities. Although Aboriginal people were, on average, younger at diagnosis with non-metastatic NSCLC than non-Aboriginal people, only 30.8 % of Aboriginal people received surgery, compared with 39.5 % of non-Aboriginal people. Further, Aboriginal people who were not receiving surgery, at the time of diagnosis, were more likely to be younger, live in major cities and have no comorbidities. The observed risk of death from NSCLC 5 years after diagnosis was higher for 266 Aboriginal people (83.3 % 95 % CI 77.5–87.7) than for 15, 491 non-Aboriginal people (77.6 % 95 % CI 76.9–78.3) and the adjusted subhazard ratio was 1.32 (95 % CI 1.14–1.52). From the medical record audit, 29 % of Aboriginal people with NSCLC had potentially curative treatment, 45 % had palliative radiotherapy/chemotherapy and 26 % had no active treatment. Conclusions There are disparities in NSCLC surgical treatment and mortality for Aboriginal people compared with non-Aboriginal people in NSW. It is imperative that Aboriginal people are offered active lung cancer treatment, particularly those who are younger and without comorbidities and are therefore most likely to benefit, and are provided with assistance to access it if required.